Variasi Pengaruh Ruang Bakar Terhadap Briket Limbah Kulit Kakao Dan Tempurung Kelapa - Mochamat Arif Efendi; Yongky Alamsyah; Izza Galang Pamungkas; Sudarno; Muhammad Hasan Basri; Doni Doni Dwi Susilo (LPPM Universitas Merdeka Madiun, 2026)
The increasing demand for energy at the national level has encouraged the development of renewable energy sources, including biomass briquettes. This study aims to analyze the characteristics of briquettes made from cocoa pod husk and coconut shell waste and to evaluate their influence on combustion chamber performance. The briquettes were produced through several stages, including carbonization for approximately 1.5 hours, grinding to a particle size of 60 mesh, and molding under a pressure of 100 kg/cm² using a starch binder with a ratio of 3:1. The results show that cocoa pod husk briquettes have an average density of 0.9575 g/cm³, influenced by a lignin content of 60.67%. These briquettes also exhibit low ash content (0.205%) and moisture content (0.1975%). In contrast, coconut shell briquettes have a lower moisture content of 0.046%, but a higher ash content of 3.058%. Both briquettes meet the SNI No.1/6235/2000 standard, with moisture content below 8%. However, despite their high calorific value, their application still faces thermal efficiency challenges due to suboptimal combustion chamber design, which results in uneven heat distribution. Therefore, optimizing combustion chamber geometry and air supply is essential.